ORGANIZATIONAL AND ECONOMIC MECHANISM FOR FORMING COMPETITIVE STRATEGIES - Kokenova A.T.; Abdikerimova G.I.; Khan I.YU.; Agabekova Sh.N.; Demeubayeva A.O. (Academic Journal of Physical and Chemical Sciences, 2020)
The stability and efficiency of the functioning of Kazakhstan’s consumer sector enterprises are currently being formed under the influence of conflicting factors of market conditions and state regulation, the convergence of which significantly determines the internal configuration, dynamics and potential for their development. The need for the development of modern, effective and adequate to the state of the markets mechanisms and instruments of strategic management was especially acute in connection with the sanction pressure of Western countries and the post-crisis transformation of micro- and mesoscale economic systems. The shortcomings of the methodological support of strategic management of the industrial business, aimed at creating long-term competitive advantages in the face of increased pressure (market and competitive) from international markets, players and regulatory institutions, became apparent. Thus, the problem of reconciling the interests of long-term strategic business development has become extremely urgent, which, as you know, is a controversial and controversial layer in domestic and foreign management science. A separate place in solving the problem of increasing the effectiveness of strategic management is occupied by issues related to ensuring high-quality strategic planning, improving organizational forms of business, the formation of motivation mechanisms for all subjects of the industrial business, as well as the development of monitoring and control systems for the implementation of development strategies. The effectiveness of the enterprise competitiveness management mechanism requires the fulfillment of certain requirements for enterprises in this field, the organizational and economic model of the enterprise, the forms and methods for evaluating the effectiveness of managerial decisions. The organizational and economic mechanism of enterprise competitiveness management is effectively implemented in management technology. In this case, we use the process approach, which allows us to consider the technology as a set of organizational measures, operations and techniques aimed at increasing the competitiveness of the service industry enterprise. The need to form an organizational and economic mechanism for the development and implementation of managerial decisions within the framework of a systematic approach to strategic management of business development as a factor in ensuring sustainable economic growth is especially relevant. These facts determined the scientific relevance and practical value of solving the problems of strategic management in industrial wineries.